Reviewing IT in due diligence : are you buying an IT asset or liability? - Wright, Christopher (Accountant); Altimas, Bryan (Fundamentals Series., 2015)
This book provides an introduction to IRM in due diligence, and outlines some of the key IT issues to consider as part of the due diligence process. For those new to the process, it explains how to conduct an IT due diligence review, from scoping to reporting, and includes information on post-merger integration to realize business benefits from the deal. For more experienced practitioners, it provides fresh insight into the process, highlighting issues that need to be addressed, and provides a business case for IRM involvement in the due diligence process. Topics include: why IT is important to due diligence; importance of IT security; system reviews and data reviews; reviewing projects and changes in progress IT service provision value for money IT due diligence reporting; post-merger integration; case studies are included throughout the book. --